Characterization and Application of TiO2/ZnO Nanoparticles as Pigments in Matt-Type Water-Based Paint - Boy Isfa; Novesar Jamarun; Emriadi; Syukri Arief; Ahmad Hafizullah Ritonga; Denny Akbar Tanjung; Vivi Sisca (International Journal of Technology, 2023)
This study investigates the characteristics of TiO2/ZnO nanoparticles and the application of TiO2/ZnO in matt-type water-based paint as a pigment. This study aims to determine the quality of TiO2-ZnO pigments in water-based paints in terms of whiteness, hiding power, dispersibility, and gloss. Matt-type water-based paint has been made by mixing water and additives substances in a high-speed mixer to result in a mill base paste, which is mixed with the pigment of TiO2/ZnO (25:75), CaCO3 filler, water, and additives, then filtered and mixed again with the C-817 binder. The characterization results showed that TiO2/ZnO nanoparticles contained TiO2 of 18.62% and ZnO of 77.49%, with an average particle diameter of 151.54 nm. TiO2/ZnO has a crystal size of 28.4 nm and a crystallinity degree of 72.3%. The application of TiO2/ZnO nanoparticles as a pigment in matt-type water-based paint resulted in good dispersion and hiding power and achieved whiteness of 82.2 and gloss at 60° of 2.00 better than TiO2 of 81.8 and gloss at 60° of 1.77.